Surgery Versus Surveillance for Well‐Differentiated, Nonfunctional Pancreatic Neuroendocrine Tumors: An 11‐Year Analysis of the National Cancer Database. (2nd October 2019) - Assi, Hussein A.; Mukherjee, Sarbajit; Kunz, Pamela L.; Machiorlatti, Michael; Vesely, Sara; Pareek, Vipul; Hatoum, Hassan
Abstract: Background: Pancreatic neuroendocrine tumors (panNETs) are a rare group of tumors that make up 2%–3% of pancreatic tumors. Recommended treatment for panNETs generally consists of resection for symptomatic or large asymptomatic tumors; however, optimal management for localized disease is still controversial, with conflicting recommendations in established guidelines. Our study aim is to compare surgical intervention versus active surveillance in nonmetastatic panNETs by size of primary tumor. Materials and Methods: Using the National Cancer Database, we identified 2, 004 patients diagnosed with localized well‐differentiated, nonfunctional panNETs (NF‐panNETs) between 2004 and 2015. Patients' clinicopathologic characteristics, treatment modalities, and overall survival (OS) were analyzed using frequency statistics, chi‐square, and Kaplan‐Meier curves. The objective of the study is to assess the outcome of surgical resection versus nonoperative management in patients with panNETs with different tumor sizes. Results: Tumor sizes were divided into three categories: <1 cm, 1–2 cm, and >2 cm. The number of patients with tumor size <1 cm, 1–2 cm, and >2 cm was 220 (11%), 794 (39.6%), and 990 (49.4%), respectively. Overall, 1, 781 underwent surgical resection, whereas 223 patients did not. Median follow‐up was 25.9 months. After adjusting for covariates, surgical resection was associated with improved OS in patients with tumor size 1–2 cm (hazard ratio [HR] = 0.37) and >2c m (HR = 0.30) but not <1 cm (HR = 2.81). Independent prognostic factors were age at diagnosis, Charlson‐Deyo comorbidity score, stage, tumor location, and surgical resection. Higher tumor grade was not associated with worse OS. Conclusion: Our findings suggest that active surveillance is potentially a safe approach for NF‐panNETs <1 cm. Larger tumors likely need active intervention. Intermediate‐grade tumors did not result in worse survival outcome compared with low‐grade tumors. Future studies might consider prospective randomized clinical trials to validate our findings. Implications for Practice: The present study seeks to address the discrepancy in treatment recommendations in the management of nonfunctional pancreatic neuroendocrine tumors (NF‐panNETs) by evaluating whether surgical resection is associated with improved overall survival in different tumor size groups as well as elucidating independent prognostic factors in patients with NF‐panNETs. Data from the National Cancer Database were reviewed. This study's findings suggest that active surveillance is potentially a safe approach for NF‐panNETs <1 cm. Larger tumors likely need active intervention. Independent prognostic factors include age at diagnosis, Charlson‐Deyo comorbidity score, stage, tumor location, and surgical resection. These findings will help guide medical and surgical oncologists when formulating treatment plans for patients with small NF‐panNETs. Abstract : Optimal management for pancreatic neuroendocrine tumors is controversial. This article evaluates whether surgical resection is associated with improved overall survival in different tumor size groups.